2015
DOI: 10.1097/ana.0000000000000131
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and Improving First Case On-Time Starts and Analysis of Factors Predicting Delay in Neurosurgical Operating Rooms

Abstract: The quality improvement project, which was implemented in 2 phases, successfully increased the FCOTS rate in our neurosurgical ORs from 33% to 68%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…The project techniques were initially tested in a single OR service. 24 Next, at multiple meetings of the OR committee and perioperative services, managers provided education about the FCOTS initiative. In addition to these educational activities, the major intervention for FCOTS improvement was to institute a 'huddle' at 9:00 AM (after the majority of first cases had started) of OR operational leaders (nursing managers, lead nurse anaesthetist, charge nurse, and anaesthesiologist in charge) to conduct a mini-root-cause analysis of each case that had started late that day.…”
Section: Process-improvement Techniques Used To Increase Fcotsmentioning
confidence: 99%
“…The project techniques were initially tested in a single OR service. 24 Next, at multiple meetings of the OR committee and perioperative services, managers provided education about the FCOTS initiative. In addition to these educational activities, the major intervention for FCOTS improvement was to institute a 'huddle' at 9:00 AM (after the majority of first cases had started) of OR operational leaders (nursing managers, lead nurse anaesthetist, charge nurse, and anaesthesiologist in charge) to conduct a mini-root-cause analysis of each case that had started late that day.…”
Section: Process-improvement Techniques Used To Increase Fcotsmentioning
confidence: 99%
“…Among the 20 included studies, nine (45%) introduced perioperative management methods in common for all elective surgeries (27)(28)(29)(30)(31)(32)(33)(34)(35). There were four studies each on preoperative methods for general surgery (36-39) and for neurosurgery (40)(41)(42)(43), two articles for eye surgery (44,45) and one article for head and neck surgery (46). Nineteen of the 20 studies investigated speci c, institution-based interventions.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…Mathews (41) reported a case control study to increase rst case on-time start (FCOTS) in the neurosurgical OT in a tertiary care centre in the USA, which was conducted in 2009 to 2011. Factors predicting delayed start were also identi ed and implemented.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…In April 2017, the Division of Perioperative Services at our tertiary-care medical center launched a multifaceted FCOTS improvement initiative. Based on best practices 3,4,[10][11][12][13] and investigation of institutional preintervention workflow, the policy comprised 3 main components: defining FCOTS and stakeholder education regarding its importance; assignment of a discrete, standardized process for preoperative workflow known as "swim-lanes" (eFig. 1); and daily reporting of FCOTS rates and sources of failure to hospital leadership and surgical, anesthesiology, and nursing stakeholders.…”
Section: Description Of Interventionmentioning
confidence: 99%
“…7 Factors associated with successful FCOTS programs include specifying a discrete definition of FCOTS, 8 early identification of factors associated with delayed starts, 9 establishing a system of data collection and monitoring, 3 and short-interval feedback to stakeholders. 10 Additionally, multiple groups have found that successful FCOTS initiatives can improve surrogate measures of OR efficiency such as FCOTS rates, 6,10,11 duration of "first start" delays, 4 and perioperative staff satisfaction. 12 Disclosure Information: Nothing to disclose.…”
mentioning
confidence: 99%